Measuring performance of CSA bundles. Technical capacity building for Zambia Accelerator Partners - Nowak, Andreea C.; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
These notes provide guidance on the process of developing an impact pathway and indicators to measure and manage investment performance. The impact investment market is valued at more than US$ 715 billion (GIIN, 2021). Global policy processes relevant to Climate-Smart Agriculture (CSA) such as the Paris Agreement and the Agenda 2030 on Sustainable Development Goals (SDGs), recognize that social, economic, and environmental objectives are interconnected and affect all actors, calling action from the impact investment community to unlock private capital to address societal challenges. This creates momentum for businesses in the food and agriculture sector to demonstrate how they create measurable social, economic, and environmental value in addition to financial returns.